2010
DOI: 10.1016/j.sjopt.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab for posterior capsule neovascularization

Abstract: We report a case of rapid regression of extensive posterior capsule neovascularization in a 67-year-old diabetic male patient, who developed posterior capsule opacity with neovascularization one year post cataract surgery, after a single injection of intravitreal bevacizumab (Avastin) followed by neodymium:YAG capsulotomy. Rapid regression of the posterior capsule neovascularization, and visual improvement was observed 9 days after the intervention. Posterior capsulotomy was performed successfully without blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The earliest case of NVPC was reported by Erig et al, in 1990, who coined the term “rubeosis capsulare” in two diabetic patients following cataract extraction. 6 While most NVPC cases since have reported the same etiology 1 , 2 , 4 , other etiologies include idiopathic ciliary body inflammation 3 , surgical interventions (pneumatic retinopexy and pars plana vitrectomy) 5 , and traumatic microcapsular breach. 7 Cases of NVPC occurring with NVI 2 , 6 and in isolation 3 , 5 have both been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The earliest case of NVPC was reported by Erig et al, in 1990, who coined the term “rubeosis capsulare” in two diabetic patients following cataract extraction. 6 While most NVPC cases since have reported the same etiology 1 , 2 , 4 , other etiologies include idiopathic ciliary body inflammation 3 , surgical interventions (pneumatic retinopexy and pars plana vitrectomy) 5 , and traumatic microcapsular breach. 7 Cases of NVPC occurring with NVI 2 , 6 and in isolation 3 , 5 have both been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported successful management of NVPC with intravitreal bevacizumab (Avastin) injections followed by Nd:YAG capsulotomy. 1 , 2 , 4 Other treatments that have been reported include photodynamic therapy followed by Nd:YAG capsulotomy 5 and vitrectomy. 6 In all these reported cases, treatment restored VA close to baseline, and no recurrence of NVPC noted on their latest follow-up visits, which ranged upwards of nine months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations